Screening for Dysplasia With Lugol Chromoendoscopy in Longstanding Idiopathic Achalasia. (June 2018) - Ponds, Fraukje A.; Moonen, An; Smout, André J. P. M.; Rohof, Wout O. A.; Tack, Jan; van Gool, Stijn; Bisschops, Raf; Bredenoord, Albert J.; Boeckxstaens, Guy E.
Abstract : BACKGROUND: Achalasia patients with longstanding disease are considered to be at risk for developing esophageal cancer. Endoscopic screening is not standardized and detection of dysplastic lesions is difficult, for which Lugol chromoendoscopy could be helpful. Aim was to evaluate the efficacy of screening for esophageal dysplasia and carcinoma in patients with longstanding achalasia using Lugol chromoendoscopy. METHODS: In this cohort study achalasia patients underwent three‐annual screening by Lugol chromoendoscopy between January 2000 and March 2016. Patients with low‐grade dysplasia (LGD) underwent yearly screening, patients with high‐grade dysplasia (HGD) or carcinoma were treated. RESULTS: In total, 230 achalasia patients (144 male, median age 52 years (IQR 43–63) at first endoscopy) were included. Three patients (1.3%, 2 male, age 68 years (range 50–87)) developed esophageal squamous cell carcinoma (ESCC), without LGD at the preceding screening. Incidence rate for ESCC was 63 (95% CI 13–183) per 100 000 persons‐years. LGD was observed in 4 patients (1.7%, 2 male, age 64 years (range 57–73)), without progression to HGD/ESCC during a follow‐up of 9 (IQR 7–14) years. ESCC/LGD was diagnosed 30 (IQR 14–36) years after onset of symptoms and 22 (IQR 4–13) years after diagnosis. Lugol chromoendoscopy tripled the detection rate of suspected lesions (111 lesions white light versus 329 lesions Lugol), but only 8% was histopathological confirmed ESCC or LGD. CONCLUSiON: Achalasia patients with longstanding disease (>20 years) have an increased risk to develop esophageal dysplasia and carcinoma. Endoscopic screening using white light and Lugol chromoendoscopy does not accurately identify precursor lesions for ESCC and therefore cannot be systematically recommended.